COMPARATIVE ANALYSIS OF GEOSPATIAL DATA COLLECTION METHODS FOR THE CONSTRUCTION OF DIGITAL MODELS OF THE LOCATION - Дорожко, Євген; Онищенко, Олександр (SWorldJournal, 2023)
The paper considers the justification of the feasibility of developing digital terrain models of linear objects on the example of highways. The main factors driving the development of digital terrain modeling today are: the rapid development of various s